Effective Modernization of the Optical Irradiating System in Greenhouse; Key Engineering Materials; Vol. 769 : High Technology: Research and Applications (HTRA 2017) - Baktybaev A. Azamat; Turanov S. B. Sergey Borisovich; Romanenko S. Sofia; Toleutaev K. Kanat (2018, 2018)
Title screen